2016
DOI: 10.1016/j.amjmed.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Emergency Department Visits and Hospitalization on Mobility Among Community-Dwelling Older Adults

Abstract: Purpose To assess effects of emergency department visits on mobility as measured by Life-Space Assessment (LSA) scores and to compare life-space trajectories associated with emergency department visit only, hospitalization, and no event. Methods 410 community-dwelling adults age ≥75 who were living in the community, able to communicate by telephone, could schedule an in-home interview, and answer questions independently were followed from June 2010-August 2014. In-home baseline and monthly telephone follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…Our MIC of five points is lower than previous estimates and suggests that while these events are associated with considerable change in life space, less dramatic events experienced by older adults may also have a significant impact on life space. Previous studies have shown that one such event, an emergency department visit, is associated with a 6.1‐point LSA decline, adding further evidence to our recommendation for a five‐point MIC.…”
Section: Discussionsupporting
confidence: 75%
“…Our MIC of five points is lower than previous estimates and suggests that while these events are associated with considerable change in life space, less dramatic events experienced by older adults may also have a significant impact on life space. Previous studies have shown that one such event, an emergency department visit, is associated with a 6.1‐point LSA decline, adding further evidence to our recommendation for a five‐point MIC.…”
Section: Discussionsupporting
confidence: 75%
“…Generalized linear mixed models (GLMMs) with a logistic link function were used to determine significant associations between life‐space at the beginning of each 6‐month interval, change in life‐space over the same 6‐month interval, and mortality over the subsequent 6‐month interval. A 10‐point difference in life‐space scores was considered clinically meaningful based on prior reports, although smaller differences may still be clinically significant . An example of a 10‐point difference would be an older person who previously reported no need for assistance to go into the neighborhood daily and to town one to three times per week (64 points) but now requires a cane to go into town less than once a week (54 points).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that they were able to maintain their life-space mobility at its previous level for longer and potentially slow down the slope of decline. It is also worth noting that the five-point decrease indicates qualitatively different changes in lifespace mobility depending on the starting value (27)(28)(29). For people who reach areas beyond their neighborhood independently (life-space mobility score over 60) a five-point decline in life-space mobility score may have rather small implications for their lives.…”
Section: Discussionmentioning
confidence: 99%